Identification of European isolates of the lager yeast parent Saccharomyces eubayanus. Issue 1 (7th December 2022) - Bergin, Sean A; Allen, Stephen; Hession, Conor; Ó Cinnéide, Eoin; Ryan, Adam; Byrne, Kevin P; Ó Cróinín, Tadhg; Wolfe, Kenneth H; Butler, Geraldine
Abstract: Lager brewing first occurred in Bavaria in the 15th century, associated with restrictions of brewing to colder months. The lager yeast, Saccharomyces pastorianus, is cold tolerant. It is a hybrid between Saccharomyces cerevisiae and Saccharomyces eubayanus, and has been found only in industrial settings. Natural isolates of S. eubayanus were first discovered in Patagonia 11 years ago. They have since been isolated from China, Tibet, New Zealand, and North America, but not from Europe. Here, we describe the first European strains UCD646 and UCD650, isolated from a wooded area on a university campus in Dublin, Ireland. We generated complete chromosome level assemblies of both genomes using long- and short-read sequencing. The UCD isolates belong to the Holarctic clade. Genome analysis shows that isolates similar to the Irish strains contributed to the S. eubayanus component of S. pastorianus, but isolates from Tibet made a larger contribution. Abstract : First isolation of European parents of lager yeasts from a wooded area on a university campus in Dublin, Ireland.